CAR, NPF, FDR, dan BOPO Terhadap Profitabilitas Bank Umum Syariah - Ellina Monica Septiani; Listyorini Wahyu Widati (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2022)
This research aims to analyze the effect of Capital Adequacy Ratio (CAR), Non-Performing Finance (NPF), Financing to Deposit Ratio (FDR) and Operating Cost of Operating Income (BOPO) on the Profitability of Islamic Commercial Banks in Indonesia. Sampling in this study used a purposive sampling method with data collection techniques, documentation studies and library research. The number of samples used as many as 12 Islamic Commercial Banks in Indonesia. The data obtained were analyzed using multiple linear regression analysis using Eviews 10 software and Microsoft Excel 365. The results of this research indicate that the CAR has an insignificant positive effect on Profitability, NPF has a significant negative effect on Profitability, FDR has an insignificant negative effect on Profitability, and (BOPO) has a significant negative effect on profitability.